Answer:
Step-by-step explanation:
Recall that an elementary matrix of a matrix operation is obtained by applying the matrix operation to the identity matrix. In this case, by replacement, it means changing the whole row of a matrix and replacing it with a the same row multiplied by a number k.
In this case, the solution is
What is the determinant of an elementary row replacement matrix?
An elementary n xn row replacement matrix is the same as the n x n identity matrix with Exactly one of the 1's replaced with some number k.This means this is the triangular matrix and so its determinent is product of its diagonal entries. Thus, the determinant of an elementary row replacement matrix is a number. Especifically, the number k we used to replace the one
1. Exactly one,atleast one
2. 1's or 0's
3. Identity matrix,invertible matrix, triangular matrix or zero matrix.
4. Product or sum
5. A number
Answer:
Th best thing would be 35% off or the blue coupon
Step-by-step explanation:
Well we can solve the orange coupon first which would be 540.37 for the final price
the blue coupon is 35 percent off or we can just multiply 815.37 by 0.65 becuase since its “off” you would only have to pay 65 percent of the item which is why I’m multiplying by 0.65. You would end up with something like 529 something which is less than 540.37
The blue coupon would be best
Also why not use both of them?
Answer:
Step-by-step explanation:
Put x = 5 to the expression 4(x - 2)(x + 3) + 7(x - 2)(x - 5) - 6(x - 3)(x - 5)
4(5 - 2)(5 + 3) + 7(5 - 2)(5 - 5) - 6(5 - 3)(5 - 5)
= 4(3)(8) + 7(3)(0) - 6(2)(0) = 96 + 0 - 0 = 96
The value of the given expression 4(x - 2)(x + 3) + 7(x - 2)(x - 5) - 6(x - 3)(x - 5) when x = 5 is 50.
The problem is asking to solve an expression for a given value of x. The given expression is 4(x - 2)(x + 3) + 7(x - 2)(x - 5) - 6(x - 3)(x - 5). We will start by substituting x = 5 into this expression.
In the first term, we substitute 5 in place of x in (x - 2) to get (5 - 2) = 3. Similarly, we substitute 5 in place of x in (x + 3) to get (5 + 3) = 8. Then, the first term becomes 4 * 3 * 8 = 96. We follow similar steps for the other two terms and calculate the values for those terms as -70 and 24 respectively. Finally, we add these three term values to arrive at the final result: "96 - 70 + 24 = 50".
#SPJ2
Answer:
Rounding to the next dollar, the total amount of interest paid by Jake is $ 923.00
Step-by-step explanation:
1. Let's review the information given to us to answer the question correctly:
Gaming system and equipment cost = $ 2,200
Annual interest rate = 28%
Monthly payment = $ 100
2. What is the total amount of interest based on the APR?
Using Excel, we calculated the total number of months to pay the gaming system and the total interest, as you can read below.
Rounding to the next dollar, the total amount of interest paid by Jake is $ 923.00
Answer: $922
Step-by-step explanation:
I just did it and got it right. make sure to put $ or you will get it wrong
Answer:
Step-by-step explanation:
Qp = charge on proton = 1.6 x 10-19 C
Qs = charge on silicon = 14 x 1.6 x 10-19 C
rf = final distance from nucleus = ∞
ri = initial distance from nucleus = (3.6 x 10-15 + 1.2 x 10-15 ) = 4.8 x 10-15 m
initial Potential energy is given as
Ui = k Qp Qs / ri = (9 x 109) (1.6 x 10-19 ) (14 x 1.6 x 10-19 ) / (4.8 x 10-15 ) = 6.72 x 10-13 J
final Potential energy is given as
Uf = k Qp Qs / rf = (9 x 109) (1.6 x 10-19 ) (14 x 1.6 x 10-19 ) / (∞) = 0 J
Change in Potential energy = ΔU = Ui - Uf = 6.72 x 10-13 - 0 = 6.72 x 10-13 J
Let the Voltage through which proton is accelerated = V
Energy gained due to potential difference = Qp V
Using conservation of energy
Qp V = 6.72 x 10-13
(1.6 x 10-19 ) V = 6.72 x 10-13
V = 4.2 x 106 volts
6x-2y=40
(6,-2)
(2,6)
(2,-6)
(-2,-6)
Answer:
The correct solutions are (6, -2).
Step-by-step explanation:
For the first equation, rearrange to make x the subject.
3x + 4y = 10
Divide the whole equation by 3 to isolate x:
Now substitute this into the second equation:
Subtract 20 from both sides:
20 - 10y = 40
20 - 10y - 20 = 40 - 20
-10y = 20
Divide both sides by 2:
-10y ÷ 10 = 20 ÷ 10
-y = 2 ∴ y = -2
Plug this value back into the first equation:
3x + 4y = 10
3x + 4(-2) = 10
3x + (-8) = 10
3x - 8 = 10
Add 8 to both sides:
3x - 8 + 8 = 10 + 8
3x = 18
Divide both sides by 3:
3x ÷ 3 = 18 ÷ 3
x = 6
Therefore, the correct solutions are (6, -2).
Hope this helps!
Step-by-step explanation:
-5/8 + 3/4
= -5/8 + 6/8
=1/8